Numerical Study on Tree Belt Impact on Wind Shear on Agricultural Land - Angel Terziev; Florin Bode; Penka Zlateva; George Pichurov; Martin Ivanov; Jordan Denev; Borislav Stankov (Applied Sciences)
Tree belts are commonly applied over agricultural terrain where seeds of wheat and other vegetation are planted in the ground in order to prevent the seeds from being blown by the wind. The tree belt comprises a long and thin (10–20 m thick) section of trees, which spans in a direction normal to the prevailing wind direction. While serving its agricultural goal, the belt does inevitably modify the boundary layer profile of the wind. This, on its part, is likely to affect the operation of small-scale wind turbines installed in the vicinity of the belt. The goal of this study is to determine the span and range at which this effect manifests itself. It was found that in the near vicinity downstream and slightly above the tree belt, the wind velocity actually increased due to the mass conservation. The flow became independent on the tree belt drag coefficient when its value was higher than 0.2 1/m. The turbulence introduced by the belt was restricted to a height of 1.5–2 tree belts.